2007
DOI: 10.1007/s10995-007-0221-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Knowledge, Attitudes, Behaviors and Training Needs Related to Infant Feeding, Specifically Breastfeeding, of Child Care Providers

Abstract: According to the results of the needs assessment, child care directors and infant room teachers are in need of current, accessible infant feeding information. Child care directors and infant room teachers desired a website with bilingual and best practice infant feeding information specific to the needs of child care providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 22 publications
2
23
0
1
Order By: Relevance
“…Our findings were consistent with other studies outcomes in the literature [27, 28, 30]. Batan et al [27] also found that good support from childcare providers at three months may help mothers to prolong breastfeeding up to six months.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings were consistent with other studies outcomes in the literature [27, 28, 30]. Batan et al [27] also found that good support from childcare providers at three months may help mothers to prolong breastfeeding up to six months.…”
Section: Discussionsupporting
confidence: 93%
“…Previous research highlights the need for provider training. Clark et al17 found that providers need not only information on best practice but also training on how and why to comply with the standard.…”
Section: Discussionmentioning
confidence: 99%
“…7 The likelihood of continuing breastfeeding is further reduced by the finding that childcare providers have inadequate knowledge of breastfeeding and other up-to-date recommendations for feeding infants. 8 Although many government entities have policies related to breastfeeding in childcare settings, there are limited data available on the breastfeeding knowledge, attitudes, and practices within childcare centers. Therefore, it is especially interesting to find two studies that gathered similar data.…”
Section: Introductionmentioning
confidence: 99%